Education and the Prison System: an analysis of public policies for access to education in prison (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2023)
This work sought to identify the public policies that provide access to education to individuals deprived of their freedom in Brazilian prisons. The specific objective was to analyze policy documents to identify the conceptions of man, world and education found in them. The data collection and analysis were supported by document analysis and the Policy Cycle approach (Mainardes; Ball and collaborators). Our results revealed the need to broaden the debate about the documents and conceptions related to prison education, which have repercussions on teachers' practical actions in the classroom. Such conceptions are based on a theoretical framework that brings the assumptions of EJA influenced by Paulo Freire's thoughts. However, they indicate that a rupture is required to move forward, aiming at a conception of education as an assured right that can generate significant changes in the lives of all subjects.Keywords: Prison Education. Youth and Adult Education. Public Policies. Right to Education.